2010
DOI: 10.1002/pola.24036
|View full text |Cite
|
Sign up to set email alerts
|

Modeling multiphase latex particle equilibrium morphology

Abstract: Multiphase waterborne polymer particles provide advantages in more demanding applications and their performance depends on particle morphology. Currently, no general approach to predict the morphology of multiphase latex particles is available. In this work, a model based on Monte Carlo methods was developed for the prediction of equilibrium morphologies of multiphase waterborne systems, such as polymer-polymer and polymer-polymer-inorganic hybrids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…As D ii = D jj = 0, only the excluded volume between the particles of one component is considered. This model potential is used because it is the simplest one that shows phase separation and more important, by just changing the D ij value, it is possible to mimic the different compatibility between the nanofiller material with the monomer and aqueous phase: the larger D ij , the lower the compatibility between the species i and j [10,11]. In the present simulations D monomer-water = 0.9 is able to reflect the insolubility of the monomer in water.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…As D ii = D jj = 0, only the excluded volume between the particles of one component is considered. This model potential is used because it is the simplest one that shows phase separation and more important, by just changing the D ij value, it is possible to mimic the different compatibility between the nanofiller material with the monomer and aqueous phase: the larger D ij , the lower the compatibility between the species i and j [10,11]. In the present simulations D monomer-water = 0.9 is able to reflect the insolubility of the monomer in water.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…The prediction of the equilibrium morphology of multiphase polymer–polymer systems by analytical minimization of the surface energy of the system is very difficult because the number of possible geometries is too high . In this case, Monte Carlo methods represent a better alternative …”
Section: Polymer–polymer Systemsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26] Several authors reported theoretical approaches aimed at predicting the particle morphology, but most of the methods are based on two limiting assumptions: either the polymer chains do not move from the point that they are formed [25,[27][28][29][30][31] or the equilibrium morphology is attained instantaneously. [11,[32][33][34][35][36][37][38][39][40] There are only few works in the literature that take into account all relevant kinetic and thermodynamic effects. Gonzalez-Ortiz et al [41][42][43] developed a model to predict particle morphology that accounted for phase separation between Polymer 1 and Polymer 2 that leads to cluster nucleation, polymerization in both clusters and matrix (Polymer 1 rich area), polymer diffusion between matrix and clusters and cluster aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium morphology of multiphase particles was predicted using Monte Carlo method. [37] Akhmatskaya et al simulated the dynamic evolution of the particle morphology of multiphase polymer-polymer and polymer-inorganic systems [44,45]using stochastic dynamics in which the movement of phases is described by the Langevin equation. The output of all these models is a very detailed description of the morphology of a single particle, which is only a partial view of a real system that is better described by a distribution of morphologies as it is illustrated in Figure 1 where the TEM micrograph of a composite latex produced in seeded emulsion copolymerization of styrene and butyl acrylate on a methyl methacrylate-butyl acrylate crosslinked seed is presented.…”
Section: Introductionmentioning
confidence: 99%